Determinan Tax Avoidance dengan Komisaris Independen sebagai Pemoderasi - Yanti, Anisyah Firda; Haryati, Tantina; Vendy, Vicky (Universitas Gorontalo, 2025)
This study employs a quantitative methodology and specifically examines the population of energy businesses that are publicly listed on the Indonesia Stock Exchange throughout the period from 2018 to 2022. This study used a purposive sampling strategy to choose a subset of 19 organizations with 95 observation data. The study incorporates the principles of agency theory and stakeholder theory. The employed methodology is panel data regression. The findings indicated that both leverage and capital intensity had no substantial impact on tax avoidance. Profitability has a negative and significant effect on tax avoidance, whereas inventory intensity has a positive and significant effect on tax avoidance. Independent commissioners lack the authority to regulate the level of borrowing and capital intensity employed for the purpose of tax avoidance. However, they possess the capability to minimize the influence of profitability and inventory intensity on tax avoidance.